Tritium Recovery Efficiency from an Array of PbLi Droplets in Vacuum. (19th May 2017) - Okino, Fumito; Frances, Laetitia; Demange, David; Kasada, Ryuta; Konishi, Satoshi
Abstract: Quantitative feasibility analysis of the tritium recovery efficiency from multiple columns of liquid PbLi droplets was conducted.Then a case study based on the HCLL specification was performed. Main concern was whether the experimentally obtained recovery efficiency from a column of droplets is applicable for the efficiency estimation from the multiple columns of droplets without any mutual degrading effects. To maintaining a safe side assumption, the tritium once released and reabsorbed on another droplet was considered to be not re-emitted while falling. By the analogy with the thermal radiation theory, the view factor which expresses the intersection ratio of radiation on another surface was applied for the estimation.The dependences on nozzle design parameters, such as nozzle pitch, number of nozzles, chamber wall clearance, and exhaust port design, were investigated. Case study results suggest that, by choosing well-suited parameters approximately 40% to 60% of the single column recovery efficiency was secured for multiple columns even on the conservative condition. The release chamber exhaust port design had a major influence. Nozzle pitch and array design have less influences, but are not negligible. However, it has to be experimentally verified to the scale-size effects and experimental programs are currently underway.